2021
DOI: 10.3390/ejihpe11040087
|View full text |Cite
|
Sign up to set email alerts
|

School Health Promotion at the Time of COVID-19: An Exploratory Investigation with School Leaders and Teachers

Abstract: The Coronavirus pandemic has impacted the entire school population’s emotions and the disruption of the organization of the school world. In this context it is important to reflect on the role of health promotion at school. The present study aimed at exploring school leaders’ and teachers’ perspectives and experiences about COVID-19 pandemic and its effects in the school and education system. The first objective was to gather the experience of school leaders regarding the change in school organization, with pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 15 publications
(13 reference statements)
1
5
0
Order By: Relevance
“…21 Due to the pandemic, reduced physical activity, irregular sleep patterns, unbalanced diet, long-term stress, and isolation negatively affected the health of students. 18 The actions of nurses in schools showed that health education played an important role in promoting physical activity, nutritional habits and social interaction, and developing healthy coping skills. 31 Health professionals during the pandemic had a significant impact on supporting student health through distance learning about health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Due to the pandemic, reduced physical activity, irregular sleep patterns, unbalanced diet, long-term stress, and isolation negatively affected the health of students. 18 The actions of nurses in schools showed that health education played an important role in promoting physical activity, nutritional habits and social interaction, and developing healthy coping skills. 31 Health professionals during the pandemic had a significant impact on supporting student health through distance learning about health.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, students’ overall health is worsening due to the pandemic. 18 This means that school nurses need a new approach for health promotion. 19 Therefore, we intended to explore the accessibility of school nurses as a health promotion tool in the context of a school pandemic.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, in the hypotheses examined, results followed the predicted pathway [ 90 , 92 ]. in previous research, they were treated as subsets of latent variables [ 93 , 94 ].…”
Section: Discussionmentioning
confidence: 99%
“…Professors who suffer high levels of indolence have a low service rate and produce a higher rate of complaints and less motivation in students. On the contrary, Evidence also indicates that resilience is essential in managing indolence in teachers [ 93 , 94 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, Sim in airway management has been adopted by many healthcare organizations and is expected to become increasingly popular in the coming years [ 6 , 7 , 15 ]. However, the coronavirus disease 2019 (COVID-19) pandemic has affected various educational settings and the availability of in-person instruction, including medical education [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 ]. Sim conducted face to face is often withheld to prevent the spread of infection between instructors and learners or between learners.…”
Section: Introductionmentioning
confidence: 99%